2015
DOI: 10.1039/c4ra15984e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and phase transition energy storage capability of a cross-linked PEG/LACE copolymer

Abstract: In this paper, the preparation of a capsule-shaped cross-linked PEG/LACE copolymer by the cross-linking reaction of polyethylene glycol (PEG) and lauric acid cellulose ester (LACE) in the presence of toluene diisocyanate (TDI) is described. Characterization by FT-IR, NMR, TEM, SEM, DSC, TG, POM and WAXD was conducted on the prepared samples to investigate their structure, phase transition energy storage capability, crystal morphology, and thermal stability. The reaction solution of PEG and LACE was extracted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Tw opeaks at q = 1.36 1/ (2q (CuKa) = 19.48 8)and at q = 1.65 1/ (2q = 23.68 8)were observed, similar to diffraction pattern of crystalline PEG. [13] When the pre-formed cubes were heated to 70 8 8Conanaluminum substrate for 1h, their cubic morphology was destroyed ( Figure S5(b)). These results imply that the evaporation-induced crystallization of PEG block of micelles is one important factor for the formation of cubes.T his crystallization is likely kinetically controlled and is constrained by the pre-assembly of the micellar aggregates under particular drying conditions.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Tw opeaks at q = 1.36 1/ (2q (CuKa) = 19.48 8)and at q = 1.65 1/ (2q = 23.68 8)were observed, similar to diffraction pattern of crystalline PEG. [13] When the pre-formed cubes were heated to 70 8 8Conanaluminum substrate for 1h, their cubic morphology was destroyed ( Figure S5(b)). These results imply that the evaporation-induced crystallization of PEG block of micelles is one important factor for the formation of cubes.T his crystallization is likely kinetically controlled and is constrained by the pre-assembly of the micellar aggregates under particular drying conditions.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In previous studies, it was reported that conventional PCMs such as paraffins (CH 3 –(CH 2 ) n –CH 3 ), poly­(ethylene glycol) (PEG), and fatty acids could be easily grafted onto cellulose or cellulosic fabrics for the fabrication of shape stable SSPCMs. However, SSPCMs synthesized in this manner are strongly rigid, even at temperatures above its phase change temperature. A lack of physical flexibility is ascribed to the low degree of grafting due to the large steric hindrance between the hydroxyl groups of cellulose and the linear chains of PCMs .…”
Section: Introductionmentioning
confidence: 99%